Do Aspirations Really Matter? - Hawkins, Cherie-Lynn (Australian and International Journal of Rural Education, 2017)
The notion of 'raising aspirations' to widen participation in higher education and increase attainment has dominated policy discourse globally for the past decade. Projects and campaigns that aim to increase participation and attainment in education therefore typically focus on student aspirations. This is certainly the case in the Tasmanian context, with the recent establishment of the Peter Underwood Centre and various other 'aspirations projects' in the state. Based on findings from a highly qualitative study in the Cradle Coast region that explored the life goals of adolescent females, this paper proposes that 'aspirations matter' as they are key motivators behind educational and career decision-making, which impacts on life chances. But the paper argues it is the capacity to fulfil them that matters equally. Personal stories and a range of artefacts were collected from the adolescent participants during life history interviews. The primary focus of the paper is to demonstrate that innovative methodologies generate more voice, which in this study allowed for a deeper understanding of life goals, influencing factors and why 'capacity' matters. Through this data collection technique, the study found that the young females had multiple aspirations, including those for higher education and these were shaped by their experiences. However, uncertainties existed around if they had the cultural or economic capital to fulfil them. The paper extends on current work in this area by demonstrating that 'capacity' is important and that there is a place for creative methods in research with rural adolescent females.